Kekuatan impak dan kekerasan komposit dengan partikel penguat dari Jamur Ganoderma Boninense - Yanhar, Muhammad Rafiq; Nasution, Ahmad Bakhori; Simamora, Mhd Syopian; Rigitta, Prinsi (Jurnal VORTEKS, 2023)
In this study, the material used was a polyester resin composite reinforced with Ganoderma mushroom powder. This study aimed to determine the impact strength and hardness of polyester resin supported with Ganoderma mushroom powder by treating it with a 5% NaOH solution. Impact and hardness test results (specimen size) will be used to determine their quality. 25% fiber and 75% polyester resin and 40% fiber and 60% polyester resin are used to make composites using various volume fraction compositions of polyester resin and mushroom powder. Meshes of 20 and 50 are used for mushroom powder. This study used ASTM E23 for mechanical testing. The 25% particle has the highest breaking energy of 46.47 kg.m2, the highest strength of 48.92 j/cm2, and decreases in the mesh of 50. The 40% particle has the highest breaking energy of 43.3 kg.m2, and the highest strength of 48.92 j/cm2. In hardness tests, mesh 20 showed the highest hardness at 25% particle volume with 11.3 HV and the highest hardness at 40% particle volume with 11.6 HV. In the test results, mesh 20 always shows the highest hardness for 25% and 40% particle volumes, respectively